(untitled) (Journal of Science and Technology, 2016)
Our premise in this paper is that the fulcrum of pedagogy is two-fold: teaching and examining. Thus, we look at some of the differences between British and American English usage, problems in the teaching situation and how teachers and examiners could handle situations where there is a mixture of British English and American or North American English. The telos of the paper is that since the medium for nearly all examinations conducted in Ghana, and much of West Af- rica is the English Language, and since many Englishes appear to be competing among them- selves for legitimacy and/or supremacy, there is an imperative need to ensure that examinees are not unduly disadvantaged. The paper explores aspects of four broad areas of English grammar where, in pedagogy, there appears a pronounced tendency to ignore the variant usages. The fo- cus is on tense, vocabulary, orthography and preposition. Each of these grammatical categories has been discussed exclusively; that is, no one discussion is contingent on the other albeit they are intertwined by the broad concept of pedagogy in English. The major question that underpins our effort is: what is the teacher and for that matter the examiner to do when caught in such a linguistic labyrinth as we often are, as far as examinations are concerned? It is suggested that as much as possible fairness in evaluating student’s essays should be the paramount objective of the teacher and the examiner. Thus, the paper argues that it is incumbent upon West African teachers and examiners to consciously educate themselves on the variant usages in the English language to ensure consistency and justice in teaching and evaluating student papers.